Production and characterization of lightweight vermiculite/geopolymer-based panels. (15th November 2015) - Medri, V.; Papa, E.; Mazzocchi, M.; Laghi, L.; Morganti, M.; Francisconi, J.; Landi, E.
Abstract: The production and the properties of lightweight composite panels, with expanded vermiculite as lightweight aggregate and geopolymer as binder, were investigated. Different compositions of the geopolymer binders (metakaolin or alumina-based) and two sizes of expanded vermiculite were tested. The produced composites were subjected to microstructural analyses, as well as to thermal and mechanical tests. Densities ranged between 700 and 900 kg/m 3, while the average strength and thermal conductivity were about 2 MPa and 0.2 W/mK, respectively. Results show that lightweight composites can be produced with satisfactory density and mechanical and thermal properties compared with other materials used in building sector, such as plasterboard or cellular concrete. Graphical abstract: Highlights: Lightweight vermiculite/geopolymer-based panels were produced. Metakaolin or alumina-based geopolymer binders were used. Densities ranged between 700 and 900 kg/m 3 . Flexural strength and thermal conductivity were 2 MPa and 0.2 W/mK.